Grasshopper on the road - Lobel, Arnold (New York : HarperCollins, 1978)
As Grasshopper sets out to follow a road, he meets some unusual characters.
Wilson's Children.
Elem. School Library Collection.
Notable/Best Books (A.L.A.).
2.4
K-3
Keywords: Grasshoppers -- Fiction; Animals -- Fiction; Grasshoppers -- Fiction; Animals -- Fiction; Animals -- Fiction; Grasshoppers -- Fiction